2015
DOI: 10.4103/0972-0707.168795
|View full text |Cite
|
Sign up to set email alerts
|

Temperature rise during polymerization of different cavity liners and composite resins

Abstract: Objective:The purpose of this study was to evaluate the thermal insulating properties of different light curing cavity liners and composite resins during light emitting diode (LED) curing.Materials and Methods:Sixty-four dentin discs, 1 mm thick and 8 mm in diameter, were prepared. Specimens were divided into four groups. Calcium hydroxide (Ca[OH]2), resin-modified glass ionomer cement, flowable composite and adhesive systems were applied to dentin discs according to the manufacturers’ instructions. The rise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The application procedures and the lower bond strength of Fuji II LC and Biodentine are reflected on the low adhesive failure modes of Fuji LC (33.3%) and Biodentine (8.3%). It is important that practitioners be familiar with the physical and mechanical properties of the cavity liners and decide which material to use depending on cavity preparation/size and the need of cariostatic properties as well as all their advantages and disadvantages 8,10,12,44) . After tooth preparation, most dentin surfaces show a smear layer 3-to 10-μm thick -an amorphous layer of inorganic and organic debris that firmly adheres to the surface and prevents resin adhesion to dentin 18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application procedures and the lower bond strength of Fuji II LC and Biodentine are reflected on the low adhesive failure modes of Fuji LC (33.3%) and Biodentine (8.3%). It is important that practitioners be familiar with the physical and mechanical properties of the cavity liners and decide which material to use depending on cavity preparation/size and the need of cariostatic properties as well as all their advantages and disadvantages 8,10,12,44) . After tooth preparation, most dentin surfaces show a smear layer 3-to 10-μm thick -an amorphous layer of inorganic and organic debris that firmly adheres to the surface and prevents resin adhesion to dentin 18) .…”
Section: Discussionmentioning
confidence: 99%
“…The use of cavity liners before restoring deep carious lesions has been widely practiced over many years 8) . Cavity liners have been described as materials that are used as a layer to seal the dentin floor from the invasion of bacteria and irritants as well as for thermal insulation [9][10][11] . These materials aim to encourage the formation of tertiary dentin and remineralization as well as improve the marginal integrity of composite restorations 8,12) .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Due to this low filler content, methacrylate-based flowable composites have lower dentin bonding strength and greater polymerization shrinkage than methacrylate-based composites. [ 2 3 ] During the polymerization of composite resins, the amount of conversion of monomers to polymers is known as the “degree of polymerization.”[ 4 ] The degree of polymerization of composite resin affects its physical and mechanical properties. In case of insufficient polymerization, problems such as marginal leakage, staining, increased erosion, water absorption, and low mechanical resistance have been reported at restoration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the past research, it was reported that the adhesive systems have no significant effect in protecting the pulp from thermal stimuli. [20][21][22] These results justify that experiments could be carried out with one sample tooth and without the use of an adhesive system.…”
Section: Discussionmentioning
confidence: 57%
“…In a study examining the temperature changes in the pulp chamber during polymerization of composite resins, it was concluded that the effectiveness of RMGICs in protecting pulp from thermal stimuli was lower than calcium hydroxide-based cements and higher than flowable composite resins; however, this study was carried out at room temperature and without simulating pulpal blood microcirculation. 21 Polycarboxylate cements are self-curing materials which can adhere chemically to tooth structures andshow high compatibility with the pulp tissue. Polyacrylic acid that is the liquid component of the material, is a weak acid and due to its large molecule structure it can not penetrate into the dentin tubules, so does not irritate pulp like other acids.…”
Section: Discussionmentioning
confidence: 99%